2003
DOI: 10.1002/chir.10264
|View full text |Cite
|
Sign up to set email alerts
|

Link between biological signaling and increased enantioseparations of acids using glycopeptide antibiotics

Abstract: The vancomycin analog A82846B has been shown to provide excellent selectivity as a chiral recognition agent for some acidic test analytes in capillary electrophoresis (CE) and high-performance liquid chromatography (HPLC). In both modes A82846B outperforms vancomycin as a chiral selector. A82846B has enhanced antibacterial activity data in comparison to vancomycin, which is probably due to the increased dimerization constant of over 100 in magnitude in comparison to vancomycin. The link between the electrophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Most important representatives of peptide chiral selectors are macrocyclic glycopeptides, vancomycin, ristocetin and teicoplanin, used for a broad class of chiral separations both in electromigration and in chromatographic techniques [293]. These selectors are mostly used in the countercurrent, partial filling mode, where the solutes reach the detection cell window after the chiral selector has been displaced from the window region, minimizing the background absorbance from the chiral selector and improving sensitivity [294] but they can be also used as immobilized chiral stationary phase in CEC [295,296]. Physically adsorbed stationary phase consisting of poly(L-lysine) and polymeric dipeptide surfactant, poly(sodium undecanoyl-L-leucyl-alaninate), has been used for OT-CEC separation of b-blockers, labetalol and sotalol, and some other chiral compounds [177].…”
Section: Chiral Analysis and Stereoisomer Separationsmentioning
confidence: 99%
“…Most important representatives of peptide chiral selectors are macrocyclic glycopeptides, vancomycin, ristocetin and teicoplanin, used for a broad class of chiral separations both in electromigration and in chromatographic techniques [293]. These selectors are mostly used in the countercurrent, partial filling mode, where the solutes reach the detection cell window after the chiral selector has been displaced from the window region, minimizing the background absorbance from the chiral selector and improving sensitivity [294] but they can be also used as immobilized chiral stationary phase in CEC [295,296]. Physically adsorbed stationary phase consisting of poly(L-lysine) and polymeric dipeptide surfactant, poly(sodium undecanoyl-L-leucyl-alaninate), has been used for OT-CEC separation of b-blockers, labetalol and sotalol, and some other chiral compounds [177].…”
Section: Chiral Analysis and Stereoisomer Separationsmentioning
confidence: 99%
“…Chiral analysis has previously been achieved using various chiral selectors such as cyclodextrins (CDs) [6][7][8][9][10], antibiotics [11][12][13][14], and crown ethers [15][16][17][18]. However, despite good chiral recognition ability, these chiral selectors have several limitations resulting from low solubility, high cost, and difficult synthetic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…One ring 2 chlorine substituent of I closely inserted into the cavity of the other molecule of the dimer [22]. Several examples of enantioresolution with vanco mycin-type chiral selectors have shown that dimerization may also increase enantioresolution for dansyl-amino acids [18,19,44]. The higher the dimerization constant, the higher the dimer concentration and thus the higher the enantioselectivity will be.…”
Section: Comparison Of the Enantioresolution R S Between I And Iiimentioning
confidence: 96%